Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan di PT. Mesin Isuzu Indonesia - Eka Safitri Anggraini; Rahmani Fitra; Roni Jarlis (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This study aims to analyze the influence of work motivation and work environment on employee performance at PT Mesin Isuzu Indonesia in 2025. In an increasingly competitive business environment, employee performance is a major factor in determining organizational success. Two variables considered important in improving performance are work motivation and work environment. This study uses a quantitative approach with a survey method by distributing questionnaires to company employees. Data analysis was carried out using the variant-based Structural Equation Modeling (SEM) technique with Partial Least Square (SmartPLS) version 3.0, through testing the path coefficient, T-statistic, and P-value. The results show that work motivation has a positive and significant effect on employee performance with a path coefficient value of 0.229, T-statistic = 3.856 (>1.96), and P-value = 0.000 (<0.05). This indicates that the higher the work motivation of employees, the higher the resulting performance. Motivation derived from job satisfaction, clear career paths, and a fair reward system are the main factors in improving performance. Furthermore, the work environment also has a positive and significant effect on performance, with a path coefficient of 0.763, a T-statistic of 12.709 (>1.96), and a P-value of 0.000 (<0.05). A comfortable and socially harmonious work environment increases employee engagement and productivity. The implications of this study emphasize the importance of creating a motivational system and a supportive work environment to support increased productivity and the achievement of organizational goals.